Recruitment of employees: Administrative burdens on Slovenian SMEs in comparison with Europe - Karin Širec Rantaša (Journal for East European Management Studies, 2004)
In recent years, the issue of administrative burden on enterprises due to legislation has received much attention. Everywhere it is acknowledged that it is important to reduce and minimize this administrative burden as far as possible, because it hinders the development of enterprises and the growth of employment. In this paper we present the required procedures governing employment regulation, the administrative burden that results out of them, and finally we draw conclusions and make some recommendations for further action in government policy in the field of hiring employees. The research has been conducted on a representative sample of Slovenian enterprises and compared with the results of The 2001 ENSR Survey on SMEs. – – In den letzten Jahren hat das Problem der administrativen Belastung auf Unternehmen aufgrund der Gesetzgebung große Aufmerksamkeit auf sich gezogen. Es ist allgemein anerkannt, dass es wichtig ist, diese Belastung so weit wie möglich zu verringern, weil diese die Entwicklung der Unternehmen und das Wachstum der Beschäftigung hemmt. In diesem Aufsatz zeigen wir die nötigen Abläufe zur Beschäftigungsregulierung auf und die bürokratische Last, die daraus resultiert und schliesslich ziehen wir ein Fazit und geben Vorschläge zur staatlichen Politik der Einstellung von Angestellten. Die Untersuchung wurde anhand einer Stichprobe unter slowenischen Unternehmen erstellt und mit den Ergebnissen der 2001 ENSR Survey on SMEs verglichen.
Keywords: 650; SMEs; entrepreneurship; administrative burden; employment